2014
DOI: 10.1094/pdis-02-14-0200-re
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Fungicides for the Control of Peronospora belbahrii on Sweet Basil in New Jersey

Abstract: 10

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 16 publications
1
16
0
1
Order By: Relevance
“…Other studies have tested some of these fungicides (McGrath, 2016a(McGrath, , 2016bMcGrath and Sexton, 2017;Raid et al, 2017), including glasshouse studies that demonstrated that fungicides mefenoxam + copper hydroxide, mandipropanid, and azoxystrobin also reduced disease (Gilardi et al, 2013). Field studies by Homa et al (2014) also showed that mandipropamid, cyazofamid, and phosphorous acid were consistently effective, whereas azoxystrobin and fluopicolide were only effective in one of two trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have tested some of these fungicides (McGrath, 2016a(McGrath, , 2016bMcGrath and Sexton, 2017;Raid et al, 2017), including glasshouse studies that demonstrated that fungicides mefenoxam + copper hydroxide, mandipropanid, and azoxystrobin also reduced disease (Gilardi et al, 2013). Field studies by Homa et al (2014) also showed that mandipropamid, cyazofamid, and phosphorous acid were consistently effective, whereas azoxystrobin and fluopicolide were only effective in one of two trials.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it may be possible to develop elite sweet basil cultivars with genetic resistance to basil downy mildew in the near future. Registered commercial fungicides, including organic production control measures (e.g., hydrogen dioxide with peroxyacetic acid, copper salts, Streptomyces lydicus) and nonorganic measures (e.g., monopotassium and dipotassium salts of phosphorus acid, potassium phosphite, and azoxystrobin) have been used with varying levels of success managing downy mildew (Gilardi et al, 2013;Homa et al, 2014;Patel et al, 2016;Pintore et al, 2016). Unregistered but effective compounds include fluopicolide, mefenoxam + copper hydroxide, and oxathiapiprolin + chlorothalonil .…”
mentioning
confidence: 99%
“…By considering the epidemiology of the seed transmitted P. belbahrii and its repercussions on control measures (Garibaldi et al 2004b;2007;Thines et al 2009), different approaches of disease management need to be evaluate. Since from the discovery of downy mildew of basil, the seriousness of the attacks and loss of production have been stimulated numerous studies in different basil production areas in the world (Gullino et al 2009;McGranth et al 2010;Mersha et al 2012;Homa et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the use of chemicals in the field is complicated by the scalar type of harvest, which makes very difficult to comply with the intervals required between the last treatment and harvest. In fact, being the causal agent of the disease very aggressive, field sprays, even when carried out with the most effective products, provide a only partial control under severe disease pressure (Gilardi et al 2013;Homa et al 2014) and are not considered the wisest control methods, because of the risk of selection of strains of the pathogen resistant to the fungicides having a specific mode of action.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are a few fungicides currently registered for controlling BDM, significant crop loss and expenses can still occur with weekly preventative fungicide applications (Homa et al, 2014). Without effective fungicide control, BDM can cause 100% crop loss (Garibaldi et al, 2007;Wyenandt et al, 2010).…”
mentioning
confidence: 99%